Juan José Arreola: un pueblerino muy universal. Ed. de Rafael Olea Franco. El Colegio de México, México, 2021; 327 pp. - Evangelista Ávila, Iram Isaí (El Colegio de México, 2023)
Juan José Arreola: un pueblerino muy universal. Ed. de Rafael Olea Franco. El Colegio de México, México, 2021; 327 pp.